2018
DOI: 10.1021/acs.jafc.8b01451
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for l-Methionine Production Catalyzed by the Aminotransferase ARO8 from Saccharomyces cerevisiae

Abstract: The aminotransferase ARO8 was proved to play an efficient role in conversion of l-methionine into methionol via the Ehrlich pathway in Saccharomyces cerevisiae in our previous work. In this work, the reversible transamination activity of ARO8 for conversion of α-keto-γ-(methylthio) butyric acid (KMBA) into l-methionine was confirmed in vitro. ARO8 was cloned from S. cerevisiae S288c and overexpressed in Escherichia coli BL21. A 2-fold higher aminotransferase activity was detected in the recombinant strain ARO8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Wagner et al reported a conversion rate of higher than 90% for l -methionine production from d , l -5-(2-methythioethyl)-hydantoin using resting cells of Arthrobacter mutant strain DSM 9771, but separation and purification of l -methionine from complex cell cultures was an issue that needed to be handled. Our previous work also reported a method for l -methionine production by in vitro catalysis of the yeast transaminases ARO8 from α-keto-γ-(methylthio) butyric acid (KMBA) and glutamate with a conversion rate of approximate 100%, but efficient preparation of KMBA in large scale is a challenge for industrial application. In comparison with the aforesaid methods, though the conversion rate is relatively low, l -methionine production from OAH and MMP has advantages in substrate availability and convenience in end-product purification.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wagner et al reported a conversion rate of higher than 90% for l -methionine production from d , l -5-(2-methythioethyl)-hydantoin using resting cells of Arthrobacter mutant strain DSM 9771, but separation and purification of l -methionine from complex cell cultures was an issue that needed to be handled. Our previous work also reported a method for l -methionine production by in vitro catalysis of the yeast transaminases ARO8 from α-keto-γ-(methylthio) butyric acid (KMBA) and glutamate with a conversion rate of approximate 100%, but efficient preparation of KMBA in large scale is a challenge for industrial application. In comparison with the aforesaid methods, though the conversion rate is relatively low, l -methionine production from OAH and MMP has advantages in substrate availability and convenience in end-product purification.…”
Section: Resultsmentioning
confidence: 99%
“…Methionine was determined by high-performance liquid chromatography (HPLC; SHIMADZU, Shanghai, China) with precolumn derivatization with 2,4-dinitrofluorobenzene (DNFB), as described by previous work. , HPLC analysis conditions were as follows: Inertsil ODS-3 column (4.6 mm × 250 mm, 5 μm, SHIMADZU, Shanghai, China); injection volume, 20 μL; oven temperature, 23 °C; flow rate, 1 mL/min; and the eluate was monitored at 360 nm. Mobile phase A (50 mM sodium acetate buffer containing 0.1% triethylamine, pH 6.4) and phase B (50% acetonitrile/50% water solution) ran on a gradient elution program (0 min, 16% phase B; 0.3 min, 16% phase B; 4 min, 31% phase B; 9.5 min, 36% phase B; 17 min, 55% phase B; 28 min, 65% phase B; 34 min, 100% phase B; 36 min, 16% phase B; 40 min, 16% phase B).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The large yellow croaker ( Larimichthys croceus ) is one of the economically most important fish species in China, with a production of 165 496 metric tons in 2016 . Similarly, pig production represents a large proportion of animal husbandry . However, in aquaculture and pig breeding, outbreaks of infectious diseases often occur .…”
Section: Introductionmentioning
confidence: 99%